Controlled synthesis of zn based nanostructure materials by electrodeposition technique for photovoltaic applications - Mohamad, Souad A. (2014)
We present here a systematic study on the synthesis thin films of various ZnO, CdO, ZnxCd1-x (O) and ZnTe nanostructures by electrodeposition technique with ZnCl2, CdCl2 and ZnSO4 solution as starting reactant. Several reaction parameters were examined to develop an optimal procedure for controlling the size, shape, and surface morphology of the nanostructure. The results showed that the morphology of the products can be carefully controlled through adjusting the concentration of the electrolyte. The products present well shaped Nanorods arrays at specific concentration and temperature. UV-VIS spectroscopy and X-ray diffraction results show that the product presents good crystallinity. A possible formation process has been proposed.